Report of the Board of Immigration (Document (Virginia. General Assembly. Senate), 1866)
1866- Report of the Board of Immigration, submitted to the General Assembly. Included were reports from the Commissioner regarding the status of emigrants to the state and what might be helpful in attracting the more favorable persons.